Determinants of digital transformation in the restaurant industry - Domingo Martin-Martin; Jose Maya Garcia; Isidoro Romero (Amfiteatru Economic Journal, 2022)
This article aims to identify the factors that influence the digital transformation process in the restaurant industry. The proposed theoretical framework differentiates three groups of conditioning factors of digitalisation in small and medium-sized enterprises (SMEs) in this sector: (1) the personal characteristics of the entrepreneurs/managers; (2) the characteristics of the businesses; and (3) the spatial location of the restaurants. The data used in the empirical research were compiled from a representative survey of restaurant SMEs in Spain. The study uses an ordinal logistic regression specification to test the hypotheses. The results obtained indicate that the education of entrepreneurs/managers, their entrepreneurial motivations, and their ambition for growth condition the digital transformation of their businesses. Furthermore, the characteristics of the company, such as the number of establishments, belonging to a corporate group, and the employees' educational level, influence the digitalisation of restaurants. Likewise, it is observed that the digitalisation process is stimulated in inland towns compared to coastal areas, as well as in intermediate municipalities with populations of between 10,000 and 100,000 inhabitants.
Keywords: R13; Z31; O30; M2; 330; digital transformation; digitalisation; innovation; restaurant; SME; Spain